Fallot’s Disease (Tetrad, Triad, Pentad) in the Structure of Congenital Heart Defects in the Azerbaijani Population - Mammad-zada, Gulnara; Qurbanova, Camila; Qasanova, Afet; Ibrahimova, Nigar; Smirnova, Elena (International Journal of Child Health and Nutrition, 2026)
Background: The aim of the study was to identify the main factors influencing the development of these heart defects, as well as to assess the demographic and medical characteristics of patients. Method: A retrospective, multicenter study was conducted across nine regions of Azerbaijan, including Baku and Sumgait, analyzing medical records from maternity hospitals and cardiology centres between 2020 and 2023. Of 2,000 confirmed CHD cases, 994 newborns had complete medical documentation and were included in the analysis. According to regional perinatal statistics, these cases corresponded to an estimated ~165,000 live births, providing population-level denominators. Clinical, demographic, maternal, and perinatal variables were analyzed using descriptive statistics, chi-square tests, and multivariable logistic regression, with odds ratios (OR) and 95% confidence intervals (CI). Results: Of the 994 CHD cases, 7.24% (n=72) had Fallot disease, including 3.82% (n=38) with Fallot triad, 2.11% (n=21) with Fallot tetrad, and 1.31% (n=13) with Fallot pentad. The incidence of CHD varied significantly by region, potentially due to differences in healthcare, genetic predisposition, and socio-economic factors. Risk factors for Fallot disease included maternal chronic diseases (35.1%), complications during pregnancy (such as pre-eclampsia, 25.5%), and obstetric interventions (18.4%). A gender imbalance was observed, with 57.3% of patients being male. The study highlighted the importance of early diagnosis, despite 70.3% of mothers undergoing antenatal check-ups, with no prenatal diagnosis of Fallot disease. Conclusions: The analysis of demographic indicators showed an imbalance in the sex ratio of patients, which may indicate varying degrees of vulnerability to the development of serious conditions. The study also demonstrated the need to improve screening programmes and expand diagnostic capabilities to detect these cardiac anomalies early. The results provide a basis for further research aimed at developing more effective methods to prevent and treat this condition, as well as to assess the long-term health consequences for patients.